Analysis The Standard of Medical Record Resources Needed, Based on Workload at Ken Saras Hospital Medical Record Instalation 2013 - Nelda Rosita Hasibuan; Lucia Ratna Kartika Wulan; Putri Asmita Wigati (Jurnal Kesehatan Masyarakat (Undip), 2014)
Background: Medical record has a purpose to achieve an orderly administrative in an increasing health effort. UU RI no. 29 of 2009 section 46 and 47 said that every doctor and dentist should be make an medical record in their practices. If they violate, they can be penalized accordance with the provisions. In this research, needs analysis seen from some aspect, the amount of resources, education, skill, and work motivation. Ken Saras Hospital Medical record installation suffer fairly high turnover in 2013, so it make increasingly heavy workload for the employees who still survive.Medical Records Installation  in Ken Sarah Hospital has been regeneration at sometime ago, so it made heavy workload for resources who still survive. .The purpose of this research is to determine the workload of resources, the suitability of the workload and the need that based on workload. Method:  This research used qualitative descriptive study with cross sectional approach. Data collection used work sampling method  and in-depth interview. The population in the study was the time used medical record personnel in completing the work and the whole effort implementing IRM in a total of 11 people. Result: The results of this research is the ideal amount of medical record resources from amount of power aspect , education, skills and nowadays work motivation of resources. According the result of this research is 3.07 hours of workload, 3.3 hours of productive time, education, skill, and work motivation affect the work system of instalation. The workload in registration section is 5.88 hours, and 5.9 hours of productive time.  Educational standards in irm is good enough, but need to add 1 resource in registration section with D3 RM standart. IRM skills is good enough, but need the training of medician recorder to improve the skill. Work motivation is still lacking. According this research, can be concluded that there's deficiency in medical record installation, 1-2 resources. The registration section with high school education competencies, need procurement training to improve the knowledge resources, and need some activities to improve work motivation